TERAPI BERMAIN MENYUSUN BALOK MENURUNKAN KECEMASAN PRASEKOLAH SELAMA HOSPITALISASI - Martasih, Endang; Sari, Ignasia Yunita; Prawesti, Indah (STIKES Bethesda Yakkum, 2023)
An introduction Hospitalization is a condition that requires children to stay in the hospital, causing anxiety.One of play therapies is block building, which is useful for improving creativity and cognitive abilities, and recognizing colors and shapes. Objective: This research aims to know the effect of block-building play therapy on anxiety of preschoolers hospitalized in Galilea 3 Children Room of Bethesda Hospital Yogyakarta. Method: This was quantitative research with quasi-experiment one group pre-posttest design. The sample was 30 children hospitalized from March 25 – May 8, 202,2 taken with consecutive sampling technique, the instrument was VAS-A questionnaire, analyzed with Wilcoxon Sign Rank Test. Results: Before therapy, 22 respondents (73.33%) experienced severe anxiety, after therapy, 17 respondents (56.6%) were not anxious. The result showedan p- value of 0.000 (p<0.05) therefore there was an effect of block-building play therapy on the anxiety of preschoolers hospitalized in Galilee 3 Children Room of Bethesda Hospital. Conclusion: There is an effect of block-building play therapy on anxiety of preschoolers hospitalized in Galilea 3 Children Room of Bethesda Hospital. Suggestion: Nurses can provide play therapy as an intervention to lower the anxiety of preschoolers undergoing hospitalization.